2009
DOI: 10.2478/v10042-009-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum cathepsin K and cystatin C concentration in patients with advanced non-small-cell lung cancer during chemotherapy.

Abstract: Abstract:A pathogenic implication of cathepsin K (Cath K) and its inhibitor -cystatin C (Cyst C) occur to be of growing importance in the mechanisms of tumor invasiveness in lung cancer. This study was conducted to investigate the prognostic role and the effects of chemotherapy on serum Cath K and Cyst C (ELISA) in patients with advanced stage nonsmall cell lung cancer (NSCLC). The study entered 40 patients (32 men) and 15 healthy volunteers (control group). Peripheral blood samples were taken before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Thus, the extent of malignancy may be thought to affect Cys-C levels. In the present study, no significant difference was found in the serum levels of Cys-C between advanced and non-advanced lung cancer patients, which was consistent with the findings in 40 non-small cell lung cancer patients reported by Naumnik et al (16). Whether the significant correlation between serum Cys-C levels and tumor extent is dependent on the original site of the cancer is beyond our current knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the extent of malignancy may be thought to affect Cys-C levels. In the present study, no significant difference was found in the serum levels of Cys-C between advanced and non-advanced lung cancer patients, which was consistent with the findings in 40 non-small cell lung cancer patients reported by Naumnik et al (16). Whether the significant correlation between serum Cys-C levels and tumor extent is dependent on the original site of the cancer is beyond our current knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, results of recent studies have shown a significant correlation between serum Cys-C levels and malignant progression in colorectal cancer, melanoma and ovarian cancer (11)(12)(13), although earlier studies reported that serum Cys-C levels were not affected by the presence of malignancies (14,15). With regard to serum Cys-C levels in patients with lung cancer, there is only one report by Naumnik et al (16). These authors reported that no correlation exists between serum Cys-C levels and staging of the disease (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro , CysC secretion is not affected by cisplatin [18], but the effect of other anti-emetics on CysC production or release is unknown. In vitro , CysC transcription is increased in numerous cancer cell lines [38, 39], and in some patients with malignancy there is increased pCysC [40, 41], which has generally correlated with burden of disease [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…In a lymph node negative population, cathepsin B protein and activity were better prognostic indicator for diseasefree survival than in the total patient population. On the other hand the expression of cathepsin B in gastric carcinoma is associated with lymph node metastasis but not with postoperative survival [20], the negative cathepsin D staining was related with one year survival in advanced squamous cell carcinoma [21] and cathepsin K and cystatin C were not predictors of the survival in patients with advanced non-small-cell lung cancer during chemotherapy [22]. In Harcbeck and al.…”
Section: Breast Cancermentioning
confidence: 99%